Histoplasmosis: An epidemiological and clinical update in China, review and a case report - Lihua Chen; Danyang Hu; Congming Zhang; Tianrui Wu; Xiangning Cheng; Ferry Hagen; Hui Zhu; Shuwen Deng (Mycology, 2024)
Histoplasmosis is a systemic mycosis caused by the dimorphic fungus in the genus Histoplasma. Histoplasmosis is overlooked in China. This study aims to provide an epidemiological and clinical update on histoplasmosis in China by literature review. We reviewed cases of histoplasmosis reported in recent 11 years  and described a case of histoplasmosis-triggered hemophagocytic lymphohistiocytosis (HLH) in an immunocompetent patient. A total of 225 cases of histoplasmosis diagnosed in China between 2012 and 2022 were involved in this study, compared with 300 cases reviewed from 1990 to 2011, an increasing number of cases of histoplasmosis have been diagnosed in the last 11 years. The majority of cases of histoplasmosis were autochthonous cases, mainly from provinces Sichuan (56/225, 24.9%), Hunan (50/225, 22.2%), Guangdong (31/225, 13.8%), and Yunnan (24/225, 10.7%). Higher incidence (52.5%, 53/99) of histoplasmosis occurred in immunocompetent patients which is similar to those from the previous 21 years, and the prevalence of the disease did not vary highly over time. Of note, the number of histoplasmosis cases is increasing, and the geographic distribution is shifting southwards over time. Improved awareness is critically important for informing clinical practice in China.